STUDI LITERATUR: MODEL PEMBELAJARAN BRAIN BASED LEARNING PADA PELAJARAN PENDIDIKAN PANCASILA DI SEKOLAH DASAR - Dina Septiana; Juhana Sakmal, Linda Zakiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Pancasila education in elementary schools plays a vital role in shaping the character of Indonesia's young generation. Its primary objective is to instill the moral, ethical, and social values of Pancasila, enabling students to become responsible and tolerant individuals. Students aged 7 to 12 are in the concrete operational stage, where they begin to think logically but struggle with abstract concepts. Therefore, engaging and interactive teaching methods are essential. The application of Brain Based Learning (BBL) serves as an effective solution to enhance student engagement by considering how the brain functions in learning. Methods such as discussions, role-playing, and hands-on experiences help students understand and internalize Pancasila values. However, challenges like students' lack of understanding and the influence of globalization need to be addressed. Thus, effective Pancasila education in elementary schools not only shapes students' character but also strengthens national identity.